Information Frictions among Firms and Households - Sebastian Link; Andreas Peichl; Christopher Roth; Johannes Wohlfart (Institute of Labor Economics (IZA), 2022)
We survey samples of German firms and households to document novel stylized facts about the extent of information frictions among the two groups. First, firms' expectations about macroeconomic variables are closer to expert forecasts and less dispersed than households', consistent with higher information frictions among households. Second, the degree of dispersion and the distance from expert forecasts varies more across groups of households than across groups of firms. Third, firms update their policy rate expectations less than households when provided with an expert forecast, consistent with holding stronger priors. Our results have implications for modeling choices, macroeconomic dynamics, and policies.
Keywords: D83; D84; E71; 330; information frictions; expectation formation; firms; households; interest rates